Analisisfaktor-Faktoryang Mempengaruhi Produktivitas Kerja Pegawai Pada Badan Pengelola Pajak Dan Retribusi Daerah Kota Bandar Lampung - Desmon Desmon; M Renandi Ekatama; Hero Desyantama (Business and Enterpreneurship Journal (BEJ), 2022)
ABSTRAKEmployee productivity can be influenced by several factors including discipline, work experience, incentives and work environment. This study aims to analyze; (1) to find out whether work discipline, work environment, incentive, and work experience partially affect the work productivity of Employees of Regional Tax and Retribution Management of Bandar Lampung City, and (2) to find out whether work discipline, work environment, incentives, and experience simulatan work affects the productivity of Management Agency Employees Regional Taxes and Retributions Bandar Lampung City. This research was conducted in April-July 2018. The location of the study in Bandar Lampung City in the City Tax and Retribution Management of Bandar City The sample of 44 respondents was chosen in a simple random manner. Data were analyzed using the Linear Multiple Regression function approach with the Ordinasy Least Square (OLS) method. The results of data analysis resulted in a multiple regression equation Y = 3.148 + 0.509X1 + 0.420X2 + 0.110X3 + 0.152X4 .. The coefficient of determination R2 was obtained at 0.569, meaning that 56.9% of the variation in the dependent variable of employee productivity can be explained by changes in independent variables for Discipline, Work Experience, incentives and Work Environment, while the remaining 43.1% is influenced by other factors. Based on the results of the F-Test, the results show that the independent variables consisting of Discipline (X1), Work Experience (X2), Incentives (X3) and Work Environment (X4) have a simultaneous effect on employee work productivity variables. Based on the t-test, each of the independent variables of Discipline (X1), Work Experience (X2), Incentives (X3) and Work Environment (X4) has a partial effect on employee work productivity variables.